Exposure and resilience of China's cities to floods and droughts: a double-edged sword. Issue 4 (4th July 2018) - Cai, Jialiang; Kummu, Matti; Niva, Venla; Guillaume, Joseph H. A.; Varis, Olli
Abstract: China's rapid urbanization in areas prone to flood or drought events can be seen as a double-edged sword. Urbanization enlarges the population exposed to these hazards, but the resulting socio-economic development also helps build resilience. This article quantifies flood occurrence, drought severity, and related resilience in 81 cities in Mainland China. The extent of flood exposure was notable, both in absolute terms as well as in relation to the drought-prone urban population. China needs to integrate urban flood/drought policy making with sustainable urbanization policy making to best contribute to minimizing flood and drought risks in its cities.